The Fedayeen in The Levant )Emergence , Castles and Architecture( )AH/1095-1273AD(488 – 672 - Abbas, Randa; SHaheen, Mohammad (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
During the Abbasid era , the second half of 5th century AH – 11th century A D , the levant ,which turned to a chessboard governed by conflicting states, suffered from crawling of Seljuk empire. This situations accompanied by the death of Fatimid calipha ( Al-mustansir) (487 AH-1094 AD). And as a sequence, the Ismaili cult splitted to Mustaali and Nizari. Nizariyya , which centered in Alamut castle, north of Persia, since 448 AH/ 1095 AD, worked to establish a state in the levant. At 535 AH/1141 AD , they bring to life a series of castlesm, named ( qelaa Alfdaoyah) , which continued alive over 130 years , depending on creating a balance between conflicting parties of Zangid Ayyubids with the Franks .When the unification of the levant and Egypt was done, under control of Mamluk , foundations of Alfdaoyah were undermined as a result. But despite its disappearance from political theatre , their castles and remains are still a witness to their excellence.